1999
DOI: 10.1152/ajpheart.1999.276.4.h1289
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of phospholipase A2attenuates functional hyperemia in the hamster cremaster muscle

Abstract: Arachidonic acid (AA) is the common precursor for several vasodilatory factors involved in the local control of blood flow. This study was designed to determine the role of phospholipase A2(PLA2) and AA release in functional hyperemia in the hamster cremaster muscle. The muscle was prepared for in vivo microscopy and subjected to electrical field stimulation for 1 min. First- and second-order arterioles dilated in response from a mean diameter of 66 ± 5 to 88 ± 7 μm ( n = 6). PLA2 was then inhibited with quina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…Similar results were also found in patients with type 2 diabetes (14). Because previous studies have supported a critical role of prostaglandin(s) in mediating functional vasodilation (10,19,20,24,30), it is possible that the impaired functional vasodilation in metabolic syndrome may be due to altered AA metabolism. Indeed, previous studies have shown that urinary thromboxane B 2 excretion is enhanced in 12-wk-old OZRs associated with an increased cyclooxygenase-2 expression in kidney (3,15).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results were also found in patients with type 2 diabetes (14). Because previous studies have supported a critical role of prostaglandin(s) in mediating functional vasodilation (10,19,20,24,30), it is possible that the impaired functional vasodilation in metabolic syndrome may be due to altered AA metabolism. Indeed, previous studies have shown that urinary thromboxane B 2 excretion is enhanced in 12-wk-old OZRs associated with an increased cyclooxygenase-2 expression in kidney (3,15).…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, the role of NO in mediating functional vasodilation in humans and animals is still unclear. Our previous study showed that, in the cremaster muscle, inhibition of cyclooxygenase with indomethacin significantly attenuates functional dilation (19,24), suggesting that prostaglandins play a central role in functional hyperemia (10). Indeed, endothelial-derived prostacyclin (PGI 2 ) has been proposed as playing an important role in regulating local blood flow during exercise through activation of PGI 2 receptors prostacyclin (IP) on vascular smooth muscle cells (20,30).…”
mentioning
confidence: 99%
“…2A, black bars). Likewise, mepacrine (10 M), at a three-to tenfold higher concentration than used in other studies to effectively block PLA 2 (1,35), produced a substantial increase in basal contraction Freq but failed to block either the positive inotropic or chronotropic effect of 10 nM SP (Fig. 2B).…”
Section: Resultsmentioning
confidence: 62%
“…2B), and the TxA 2 synthase inhibitor imidazole. Although we do not have independent confirmation of the effectiveness of these inhibitors, we used a threefold higher dose of indomethacin that completely blocked the SP action in guinea pig lymphatics (39), a three-to tenfold higher dose of mepacrine than required to block PLA 2 in other studies (1,35), and the same dose of imidazole that blocked SPinduced lymphatic chronotropy in guinea pig (39). It should be noted that flow-dependent diastolic relaxation in the rat thoracic duct was independent of COX activity as well (13).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, functional hyperemia in the hamster cremaster muscle was inhibited by global administration of the cyclooxygenase inhibitor indomethacin (19,34) or by the phospholipase A 2 inhibitor, quinacrine (39), which blocks the liberation of arachidonic acid from the cell membrane. As these inhibitors were applied to the whole cremaster muscle, it is possible that the arachidonic acid metabolites were coming from locations other than the venular endothelium.…”
Section: Physiological Role For Venular-arteriolar Communicationmentioning
confidence: 99%